Comparison of Dutch healthy eating and healthy eating indexes and anthropometry in patients with major depression with health subjects: a case-control study - Tohidi Nafe, Melika; Movahedi, Ariyo; Djazayery, Abolghasem (Frontiers in Nutrition, 2024)
Background: Diseases and disorders related to mental health are spreading like other chronic diseases all around the world. Considering the role of food in the prevention and treatment of these disorders, including major depression, investigating the relationship between different food patterns and this disorder is of particular importance. The aim of this study was to compare Dutch healthy eating and healthy eating indexes and anthropometry in patients with major depression with healthy individuals.Methods: In this case-control study, the final analysis was performed on 67 men and 111 women with an age range of 20-30 years. Height (cm), weight (kg), food frequency questionnaire (FFQ), physical activity (MET-min/week), demographic and PHQ-9 questionnaires were taken from all participants. In the following, all the food ingredients and their components were extracted and used to calculate HEI-2015 and DHD. Statistical analysis was performed using SPSS software with independent t-test, logistic regression and chi-square.Results: It was found that people with major depression in this study were mostly women and occupied. The average HEI-2015 in healthy people and those with major depression was 58 and 54.3, respectively. Also, the average DHD in these people was 60.5 and 55, respectively. HEI-2015 and DHD had a significant negative correlation with depression score (r= -0.16, p-value= 0.03) (r= -0.19, p-value= 0.01). Also, in the logistic regression model, before and even after adjusting confounders, HEI-2015 and DHD had a reduced odds ratio in people suffering from major depression. The two groups did not differ significantly in terms of the average factors of height, weight and body mass index (BMI).Conclusion: It seems that HEI2015 and DHD have a significant relationship in reducing major depression. However, due to the small number of studies in this regard, especially in the field of DHD, the need for more studies seems necessary.